Analisis Faktor yang Mempengaruhi Standar Waktu Pelayanan Truck Round Time PT Terminal Peti Kemas Surabaya - Yasmine Mutiara Lintang; Bugi Nugraha; Akhmad Kasan Gupron (Jurnal Bintang Pendidikan Indonesia, 2024)
The aim of this research is to determine the performance of TRT from 2021 to 2023, identify the causes and impacts of TRT that exceeds the standard set time. The research design used is descriptive research with a mixed methods approach (qualitative )The type of data used is qualitative and quantitative data presented in numbers and sentences that support the author's opinion in analyzing this research. Data sources in this research are divided into primary data sources obtained from interviews, observations and literature studies and secondary data sources obtained from company data in the form of throughput data, TRT for 2021 to 2023, printed books, journals and the internet. The results of this research are that the TRT performance at PT Terminal Petikemas Surabaya is good because in 2021 to 2023 the dominant number of trucks at the TRT was less than 30 minutes, although there could be indications of a decline in performance. This decline in performance is indicated by an increase in the number of trucks from 2021 to 2023 on TRT of more than 30 minutes. The causes of TRT exceeding the standard determination time are density factors in the stacking yard, equipment factors (service and availability), human resource factors and natural factors. The negative impact of TRT that exceeds the standard set time is disruption of loading and unloading activities, internal company losses and decreased customer loyalty. Suggestions that can be used in overcoming TRT (Truck Round Time) problems are that good coordination is needed in accordance with Standard Operating Procedures (SOP), good improvisation from human resources, systems and equipment as well as yard planners carrying out various plan innovations by shortening slots so that RTG movements are not too displacement length.